Copy Number Profiling of Brazilian Astrocytomas. Issue 7 (1st July 2016) - Bidinotto, Lucas Tadeu; Torrieri, Raul; Mackay, Alan; Almeida, Gisele Caravina; Viana-Pereira, Marta; Cruvinel-Carloni, Adriana; Spina, Maria Luisa; Campanella, Nathalia Cristina; Pereira de Menezes, Weder; Clara, Carlos Afonso; Becker, Aline Paixão; Jones, Chris; et al.
Abstract: Copy number alterations (CNA) are one of the driving mechanisms of glioma tumorigenesis, and are currently used as important biomarkers in the routine setting. Therefore, we performed CNA profiling of 65 astrocytomas of distinct malignant grades (WHO grade I–IV) of Brazilian origin, using array-CGH and microsatellite instability analysis (MSI), and investigated their correlation with TERT and IDH1 mutational status and clinico-pathological features. Furthermore, in silico analysis using the Oncomine database was performed to validate our findings and extend the findings to gene expression level. We found that the number of genomic alterations increases in accordance with glioma grade. In glioblastomas (GBM), the most common alterations were gene amplifications ( PDGFRA, KIT, KDR, EGFR, and MET) and deletions ( CDKN2A and PTEN) . Log-rank analysis correlated EGFR amplification and/or chr7 gain with better survival of the patients. MSI was observed in 11% of GBMs. A total of 69% of GBMs presented TERT mutation, whereas IDH1 mutation was most frequent in diffuse (85.7%) and anaplastic (100%) astrocytomas. The combination of 1p19q deletion and TERT and IDH1 mutational status separated tumor groups that showed distinct age of diagnosis and outcome. In silico validation pointed to less explored genes that may be worthy of future investigation, such as CDK2, DMRTA1, and MTAP . Herein, using an extensive integrated analysis, we indicated potentially important genes, not extensively studied in gliomas, that could be further explored to assess their biological and clinical impact in astrocytomas.